Acoustic Assaults on the Auschwitz-Birkenau Concourse - Sewell, Sara Ann (Holocaust and genocide studies, 2024)
This article investigates how sonic encounters shaped Jews’ experiences on the concourse at Auschwitz-Birkenau. By applying methods associated with sound and sensory studies, the article examines survivors’ memoirs and interviews to demonstrate that sonic violence was a key aspect of the genocide. The train ramp was a dynamic acoustic environment in which interlocking noises swelled and contracted as part of the arrival operation. As Jewish arrivals deboarded the trains, an array of threatening noises battered them, including amplified commands blasted in German, antisemitic slurs, vicious barking, beatings, and gunshots. SS guards used these acoustic assaults to perpetrate sonic violence against the arrivals, subduing their targets by instilling fear through sound. By generating an atmosphere of chaos and confusion through sound, they achieved their chief objective: prisoner compliance. Acoustic assaults inflicted somatic and psychological pain that manifested itself physically. Many deportees responded to the sensorial onslaught with their own sonorous outpourings. Cries, wails, and screams flooded the concourse, evidence of their trauma. Besieged sensorially, many became mentally immobilized, underlining the capacity of sonic violence to impair cognition. Their mental paralysis amid the cacophonous maelstrom marked their shattered subjectivities, which seared themselves sonically into their memories.